(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Schiff base derived from 2-aminophenol and 2-hydroxy-6-methoxy-3-quinolinecarboxaldehyde and its Co(II) and Ni(II) complexes were synthesized and characterized by elemental analysis, melting point and decomposition temperature, molar conductivity, IR spectral analysis, AAS analysis, solubility test, and magnetic susceptibility. The FTIR spectral data of the Schiff base determined showed a band at 1622cm-1 which was assigned to the v(C=N), a feature of azomethine group. The same band was observed to shift to lower frequencies 1577 and 1599cm-1 in the complexes suggesting coordination of the Schiff base with the respective metal (II) ions. Molar conductance values 14.58 and 12.65Î©-1cm2mol-1show that the metal complexes were non-electrolytic in nature. The magnetic susceptibility of the complexes were determined and the gram magnetic susceptibility of the complexes were found to be positive, revealing that they are paramagnetic. The elemental analysis of the complexes for C, N and H determined suggested (1:1) metal to ligand ratio. The result of the antimicrobial studiesthat, the metal (II) complexes exhibited higher antibacterial and antifungal activity than the Schiff base but lower than the reference drugs Amoxicillin and Ketoconazole used as control in all cases.